Mighty Mount Kilimanjaro - Chiavini, Lorenzo; Ronchi, Roberto; Bigolin, Silvia (New York : Scholastic, 2010)
Bruce Hyena convinces Geronimo to join him in climbing Mount Kilimanjaro, a task for which the mouse journalist is completely unprepared.
"English translation ... by Atlantyca S.p.A."--T.p. verso.
G4
Keywords: Mice -- Fiction; Mountaineering -- Fiction; Kilimanjaro, Mount (Tanzania) -- Fiction; Mystery fiction